2003
DOI: 10.5688/aj670376
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation Processes for an Objective Structured Clinical Examination (OSCE) for Entry-to-Practice Certification in Pharmacy: The Canadian Experience

Abstract: Objectives. An objective structured clinical examination (OSCE) was developed and validated as an addition to the entry-to-practice examination for pharmacists that previously consisted of both a multiple-choice, case-based written test of clinical knowledge and a performance assessment. Methods. Designing the OSCE for entry-to-practice certification of pharmacists in Canada required extensive consultation with stakeholders, development of an examination blueprint outlining competencies to be assessed, careful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 16 publications
2
98
0
1
Order By: Relevance
“…Moreover, our consultations during the development process led to our decision to allocate 15 minutes per station because similar tasks were given less or equal time limits elsewhere. 2,4,6,10,20 Standard setting procedures such as Angoff and borderline were not utilized in the examination, since ours was a pilot study. In the future we hope to use such methods for grading performance and testing validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our consultations during the development process led to our decision to allocate 15 minutes per station because similar tasks were given less or equal time limits elsewhere. 2,4,6,10,20 Standard setting procedures such as Angoff and borderline were not utilized in the examination, since ours was a pilot study. In the future we hope to use such methods for grading performance and testing validity.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5] In fact, the OSCE has been proven and rated as the most reliable and valid tool for assessing clinical competency. [6][7][8] The Kulliyyah (ie, the Faculty) of Pharmacy at the International Islamic University Malaysia (IIUM) has taken a pioneering role during the 2005-2006 academic session by applying and evaluating the effectiveness of this assessment instrument among the fourth-year students for the final examination in clinical pharmacy. This method was introduced to our undergraduate program in the context of a desire to improve the quality of our evaluation techniques and ever-changing curriculum, and to be abridged of current instructional technologies in pharmaceutical education.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Although a larger number of stations has been used to increase the reliability of OSCE in a highstake setting (such as The Pharmacy Examining Board of Canada's Qualifying Examination), 14 a small OSCE station number, in conjunction with the written exam, can serve as a reliable, valid and economically feasible global assessment method of student performance. 18,20 Although we did not conduct any interrater reliability testing, the similarity in the exam scores indicated that the interrater and interpatient variability didn't affect reliability of the exam.…”
Section: The Interpatient and Interrater Variabilitymentioning
confidence: 99%
“…7,[10][11][12] Colleges and schools of pharmacy have adapted and refined the innovation for use in performance-based assessment of pharmacy students. 13,14 The more inclusive term standardized client was chosen for the Kansas program to accommodate a broader set of assessment scenarios. By the early 2000s, US and Canadian medical and Canadian pharmacy license examinations required candidates to complete simulated live clinical encounters.…”
Section: Introductionmentioning
confidence: 99%